A Curse Against the Greens - Németh, György; Barta, Andrea (Acta Classica Universitatis Scientiarum Debreceniensis, 2025)
The curse tablet presented in this study is part of the collection of Musée Bargoin in Clermont-Ferrand. After its discovery in 1906, it was forwarded to Auguste Audollent for examination. However, no scholarly investigation has been conducted on the tablet since then, and it has not been published, save for a short reference. The tablet, as indicated by its inscription, may have been made with the intent of influencing the outcome of a North African chariot race involving the Green team.